Design of a high gain & ultra wideband microstrip array antenna for avalanche radar - Farah Nadia, Mohd Isa; Paul V., Brennan (2011)
This paper presents the design and construction of a microstrip array antenna operating at 5.3 GHz, to be used as an avalanche sensor in avalanche measurement. The advantage of the antenna is it can achieve a high gain of 15.6 dB with bandwidth of 90%. This was achieved by separating the feed network from the main patches; and increasing the antenna height by installing the feed layer at the back of the patch layer, sharing the same ground plane. In order to ensure the power is transferred smoothly from the main input port, the feed is design in novel spider like tapered feed network while ensuring the overall antenna function is not compromised. © 2011 IEEE.